2020
DOI: 10.1101/2020.01.20.913129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spinach Growers Value Host Resistance and Synthetic Fungicides in the Fight against Downy Mildew

Abstract: California spinach growers struggle to manage spinach downy mildew disease. The disease is especially difficult in the organic crop, which currently relies on resistant varieties to maintain disease-free crop. Alternative control measures are available, but it is not clear how growers perceive the efficacy of these methods. It is also not clear who growers contact to find out information on spinach downy mildew disease management. In this study, we conducted an online survey of people involved in spinach produ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This proportion is lower than those found in other studies. Choudhury et al (2016) found that 31.7% of fields surveyed for spinach downy mildew had disease incidence greater than 0.1%. Our participant's estimate for disease affected fields may be lower because they do not count fields that had only small patches of disease, or that they were unable to detect disease due to insufficient surveillance.…”
Section: Demographics Of Participantsmentioning
confidence: 95%
See 2 more Smart Citations
“…This proportion is lower than those found in other studies. Choudhury et al (2016) found that 31.7% of fields surveyed for spinach downy mildew had disease incidence greater than 0.1%. Our participant's estimate for disease affected fields may be lower because they do not count fields that had only small patches of disease, or that they were unable to detect disease due to insufficient surveillance.…”
Section: Demographics Of Participantsmentioning
confidence: 95%
“…In the future, surveys can be conducted to explore producer's willingness to pay and adopt alternative management practices, like resistant seeds developed with CRISPR technology (Kock et al 2019), spore trapping (Choudhury et al 2016a), mixes of resistant and susceptible varieties (Choudhury et al 2016b), oospore seed thresholds (Choudhury et al 2017a), and organic pesticides (Choudhury et al 2015a;Choudhury et al 2017b). These studies could be conducted online or in person.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetable crop residues are usually incorporated into the soil shortly after the harvest in order to minimize the risk of infection by plant pathogens such as damping-off diseases and downy mildew in spinach crop rotations [9,19,20]. However, spinach crop residues are characterized by a low carbon (C) to N ratio which accelerates net mineralization and nitrification after incorporation into the soil.…”
Section: Introductionmentioning
confidence: 99%